Persepsi Orang Tua Terhadap Cara Menstimulasi Otak Anak Melalui Permainan Puzzle - ., Putri Sabrina Artamevia; ., Yosi Nur Annisa Amanda; ., Ines Kusnun Saranuha; ., Rita Tresnawati; ., Masyunita Siregar (CV. ITTC INDONESIA, 2023)
Children who receive less brain stimulation, their development will be hampered. This has an impact on his future because brain damage early on is more difficult to repair. Children who get stimulation according to their brain development will be more successful in school. This research methodology is a descriptive research with a quantitative strategy. The questionnaire provided consists of 6 questions with 10 alternative answers. The results showed that 100% of respondents said puzzle games could improve short-term memory skills. 100% of respondents said puzzle games could train children to solve a problem. In the statement the level of difficulty (level) in the puzzle game does not have to be in accordance with the child's age, 62.57% of respondents said it was wrong and 37.5% of respondents said it was correct. 100% of respondents said puzzle games can train children's brain cells to develop their thinking and concentration abilities. As many as 100% of respondents stated that puzzle games were able to develop children's creativity and imagination. As many as 100% of respondents stated that children learn to recognize different shapes, sizes, and colors in each object. It can be concluded that all respondents are good. Parental influence, involvement, and guidance are essential for healthy braindevelopment. So the results of the analysis above as seen from the respondents show that pizzles can encourage children's brain development.